2020
DOI: 10.1371/journal.pone.0239369
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanoparticles as antigen vehicles to induce effective tumor specific T cell responses

Abstract: Cancer vaccinations sensitize the immune system to recognize tumor-specific antigens de novo or boosting preexisting immune responses. Dendritic cells (DCs) are regarded as the most potent antigen presenting cells (APCs) for induction of (cancer) antigen-specific CD8+ T cell responses. Chitosan nanoparticles (CNPs) used as delivery vehicle have been shown to improve anti-tumor responses. This study aimed at exploring the potential of CNPs as antigen delivery system by assessing activation and expansion of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…In addition, the chitosan (CS) could enhance the general cell-mediated and humoral immunity after intestinal absorption when it became soluble at pH higher than 5. Afterward, CS could be considered as a biological modifier in the case of cancer due to the enhancement of the body immune cells (T-cells and natural killer cells) and antibody production to capture the cancer cells or the apoptotic cells after the absorbed ABX nanoparticles action [ 21 ]. The inclusion and release of the ABX were as nanoparticles from the suspension after raft/floating gel formation at the stomach.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the chitosan (CS) could enhance the general cell-mediated and humoral immunity after intestinal absorption when it became soluble at pH higher than 5. Afterward, CS could be considered as a biological modifier in the case of cancer due to the enhancement of the body immune cells (T-cells and natural killer cells) and antibody production to capture the cancer cells or the apoptotic cells after the absorbed ABX nanoparticles action [ 21 ]. The inclusion and release of the ABX were as nanoparticles from the suspension after raft/floating gel formation at the stomach.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the mucosal route, chitosan-cloaked nanoplatforms can be transferred into immune-competent cells to foster cellular immune responses. By tuning the size of chitosan nanoparticles, Walter and coworkers explored the potential of chitosan nanoparticles as antigen vehicles to deliver ovalbumin-derived peptide SIINFEKL (OVA 257–264) into tumor tissue for a potent immune response [ 60 ]. It was observed that DCs could effectively take up the chitosan-based nanoparticles with small particle sizes, generally regarded as the most potent APCs to induce activation and proliferation of tumor antigen-specific CD8 + T cells.…”
Section: Immune-regulating Camouflaged Nanoplatformsmentioning
confidence: 99%
“… Eliciting an antitumor immune response Immunotherapy Chitosan nanoparticles of small size were confirmed to act as suitable antigen vehicles to induce activation and proliferation of tumor antigen-specific CD8 + T cells. [ 60 ] A core-shell gold nanocage coated with manganese dioxide and HA (AMH). Evading immune elimination/tumor targeting PDT and ICD-elicited immunotherapy AMH nanoparticles with biocompatibility demonstrated targeting ability towards CD44-overexpressing cancerous cells and oxygenation-boosted immunogenic phototherapy in situ .…”
Section: Applications In Cancer Nano-immunotherapymentioning
confidence: 99%
“…61 Thus, considering the nanostructures can be made to also include antigens, the design of PSA–polymer conjugates presents an attractive for designing novel vaccines or nanotherapeutics for infectious diseases. 45,62,63 Moreover, synthetic polymers can be designed to incorporate biodegradable linkages into the backbone chain which would ensure they also undergo degradation like the carbohydrates and ensure clearance of the materials. 64 Thus, the materials can be designed to be safe and compatible with in vivo applications akin to carbohydrates.…”
Section: Introductionmentioning
confidence: 99%